Divulgação de informações voluntárias sobre o meio ambiente: uma análise dos fatores diferenciadores - Coelho, Fernando Quaresma (Universidade do Vale do Rio do Sinos, 2010)
This study analyzes the differentiation factors of the level of disclosure of volunteer information about the environment by Brazilian joint stock companies belonging to sectors of high environmental impact. Considering the disclosure theory, seven variables were formulated: dimension, profitability, debt, corporate governance, sustainability, stock control and internationalization; they aim to establish the relationship with the level of environmental disclosure. Through content analyze technique of the Financial Demonstrations Patterns (FIPs) ended in 2008 it was examined information of environmental nature published by 69 companies that have shares listed in the Stock Exchange of São Paulo (BOVESPA), classified according Attachment VIII of the Law n°. 10.165/2000. Afterwards, it was identified the differentiation factors that explain the disclosure of environmental information by statistical technique of multiple regression. The results reveal that the information verified in the FIPs figurate, in general,
Keywords: fatores diferenciadores do nível de divulgação; setores de alto impacto ambiental; divulgação ambiental; differentiation factors of the disclosure level; sectors of high environmental impact; environmental disclosure; Ciências Sociais Aplicadas